Kecenderungan Perilaku Pelecehan Seksual Remaja - N, Lani Zefania; Karneli, Yeni (Lembaga Yasin AlSys, 2024)
This research is motivated by adolescents who have a tendency to sexual harassment behavior caused by adolescents having high curiosity and thinking about sexuality, as well as the influence of the environment and social media. Thus causing adolescents to want to imitate the behavior they see both around them and the behavior they see from social media. This study aims to describe: 1) a description of the tendency of adolescent sexual harassment behavior in SMPN 40 Padang as a whole, 2) a description of the tendency of adolescent sexual harassment behavior in SMPN 40 Padang in terms of behavioral aspects, 3) a description of the tendency of adolescent sexual harassment behavior in SMPN 40 Padang. The research method used is quantitative method with descriptive approach. The sample in this study were 180 students in grades VII & VIII at SMPN 40 Padang in the 2023/2024 school year, who were selected using the Simple Random Sampling technique. Data obtained by giving research instruments in the form of a sexual harassment questionnaire to junior high school students who have been tested for validity with the pearson correlation formula (0.361) and reliability testing with the Cronbach alpha formula (0.736) to students. For data processing using descriptive statistical methods. The results showed that: 1) The tendency of adolescent sexual harassment behavior in terms of behavioral aspects is in the low category, meaning that adolescents tend to have committed some sexual harassment behavior, 2) The tendency of adolescent sexual harassment behavior based on situational aspects is in the low category, meaning that adolescents tend to have committed some sexual harassment behavior in public places such as school. Overall, adolescents have a low tendency of sexual harassment behavior, this shows that adolescents tend to have committed some sexual harassment behavior. Based on the results of this study, counselors can provide assistance to prevent sexual harassment behavior in adolescents in the form of information services about understanding sexual harassment, types of sexual harassment, the impact of sexual harassment behavior, and how to avoid sexual harassment behavior. Another service provided to students is group guidance services, where students led by bk teachers / counselors in groups discuss the phenomenon of sexual harassment among adolescents so that adolescents can understand how sexual harassment behavior occurs around them and how to prevent sexual harassment behavior.